The idiomaticity of the English language / Hajibah Osman - Osman, Hajibah (Institut Teknologi MARA Cawangan Sarawak, 1990)
Most students of English as a second or foreign language believe that they have mastered the language when they can express themselves fluently and grammatically, and that it is not necessary for them to learn the language frills such as the colloquial forms and the idiomatic expressions. These students view the formal nature of the colloquial and idiomatic expressions as irrelevant in the process of acquiring the target language. On the contrary, idiomatic expressions form very important part of the English language. They give life and richness to the language by enabling it to absorb new concepts which need to be expressed linguistically in a different and more interesting way. Idiomatic expressions are widely used by most native speakers of English in their everyday conversations.